Characterization of memory profile in idiopathic REM sleep behavior disorder. Issue 3 (16th March 2022) - Wenke, Štěpán; Mana, Josef; Havlík, Filip; Cohn, Melanie; Nikolai, Tomáš; Buschke, Herman; Nepožitek, Jiří; Peřinová, Pavla; Dostálová, Simona; Ibarburu Lorenzo Y Losada, Veronika; Růžička, Evžen; Šonka, Karel; et al.
ABSTRACT: Objective: The present study aims to examine whether declarative memory dysfunction relates to impaired core memory mechanisms or attentional and executive dysfunction in idiopathic REM Sleep Behavior Disorder (iRBD). Method: In this observational, cross-sectional study, were enrolled 82 individuals with the diagnosis of iRBD according to the International Classification of Sleep Disorders and 49-matched healthy controls fulfilling inclusion criteria. All participants underwent two memory tasks, namely the Rey Auditory Verbal Learning Test (RAVLT) and Memory Binding Test (MBT), which include conditions of varying degrees of dependence on executive functioning, as well as different indicators of core memory processes (e.g., learning, retention, relational binding). Results: We used Bayesian multivariate generalized linear model analysis to evaluate the effect of iRBD on memory performance controlled for effects of age and sex. Individuals with iRBD displayed worse memory performance in the delayed free recall task ( b = −0.37, 95% PPI [−0.69, −0.05]), but not on delayed recognition of the same material. Their performance in cued recall tasks both in immediate and delayed conditions was in comparison to controls relatively spared. Moreover, the deficit in delayed free recall was mediated by attention/processing speed. Conclusions: In iRBD, we replicated findings of reduced free recall based on inefficient retrieval (retrieval deficit), which was small in terms of effect size. Importantly, the memory profile across measures does not support the presence of core memory dysfunction, such as poor learning, retention or associative binding. Graphical abstract: uf0001